Back Cover: Luminescent Thin Films Composed of Nanosized Europium Coordination Polymers on Glass Electrodes (ChemPlusChem 2/2016). Issue 2 (26th November 2015) - Hasegawa, Yasuchika; Sugawara, Takeshi; Nakanishi, Takayuki; Kitagawa, Yuichi; Takada, Makoto; Niwa, Akitsugu; Naito, Hiroyoshi; Fushimi, Koji
Abstract : The cover picture shows luminescent thin films composed of lanthanide coordination polymers on a glass electrode. The luminescent thin films are prepared using micelle techniques in water media. Thermostable thin films of Eu III coordination polymers on electrodes are expected to open up a new field spanning inorganic chemistry, electrochemistry, and materials and colloid science. More details can be found in the Full Paper by Yasuchika Hasegawa et al. onpage 187 in Issue 2, 2016 (DOI:10.1002/cplu.201500382 ).